Who gets the Reward? An Empirical Exploration of Bonus Pay and Task Characteristics - Wendelin Schnedler (Institute for the Study of Labor (IZA), 2000)
Contract theory predicts that workers are remunerated based on all available unbiased individual performance measures. In the real world, measures are often biased: tasks are too complex to include all measures, unforeseen contingencies occur for which contracts specify nothing, and the necessity of cooperation and coordination at tasks would be undermined by purely individual measures. Hence, alternative incentive mechanisms are employed (implicit contracts, efficiency wages, wage profiles, tournaments). This suggests that bonus pay is linked to task characteristics: complex tasks will be negatively related to bonus pay, unforeseen contingencies and the necessity to cooperate or coordinate will be positively correlated to premiums on aggregated levels such as team or firm bonus. The present article explores these relations using a French cross-sectional micro-data set. While complexity is found not to be negatively related to bonus pay, the other two effects are supported by the data.
Keywords: J33; 330; Incentive schemes; bonus pay; three-variate probit; Leistungsorientierte Vergütung; Anforderungsprofil; Leistungsanreiz; Anreizvertrag; Schätzung; Frankreich